El trabajo como posicionamiento existencial y medio productor de identidad en la poesía bribri de lo cotidiano - Solano Fallas, Andrés (2017)
On Poesía bribri de lo cotidiano (Bribri poetry of the daily day), the topic of work is presented as a fundamental axis of the daily day conception. Given this, the exposition has for objective to explore the philosophical importance of work as existential positioning in the world and as a mean to produce identity, despite the existence of a destiny that directs the person towards his encounter with the divinity. First, starting from the singings of Poesía bribri de lo cotidiano, it will be defined the concept of destiny and its link with the divinity, because it constitute a conditionant of the person’s existence and identity. Second, it will be explained what is work and which is its importance on the daily day, given that on the bribri cultural conception, the daily day existence is a temporal step of the human existence.